2014
DOI: 10.1002/2013jd020631
|View full text |Cite
|
Sign up to set email alerts
|

First simultaneous measurements of ozone, CO, and NOy at a high‐altitude regional representative site in the central Himalayas

Abstract: Simultaneous in situ measurements of ozone, CO, and NO y have been made for the first time at a high altitude site Nainital (29. 37°N, 79.45°E, 1958 m above mean sea level) in the central Himalayas during [2009][2010][2011]. CO and NO y levels discern slight enhancements during the daytime, unlike in ozone. The diurnal patterns are attributed mainly to the dynamical processes including vertical winds and the boundary layer evolution. Springtime higher levels of ozone (57.5 ± 12.6 ppbv), CO (215.2 ± 147 ppbv),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
79
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 106 publications
2
79
0
Order By: Relevance
“…It was shown that the anthropogenic emissions and their subsequent photochemical degradation over south Asia influence air quality over the Himalayas (e.g. Ojha et al, 2012;Sarangi et al, 2014) and the Tibetan Plateau (Lüthi et al, 2015) as well as the marine environment downwind of India (e.g. Lawrence and Lelieveld, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the anthropogenic emissions and their subsequent photochemical degradation over south Asia influence air quality over the Himalayas (e.g. Ojha et al, 2012;Sarangi et al, 2014) and the Tibetan Plateau (Lüthi et al, 2015) as well as the marine environment downwind of India (e.g. Lawrence and Lelieveld, 2010).…”
mentioning
confidence: 99%
“…These results indicate the need for evaluating the effects of emission inventories and chemical mechanisms on the model performance using a network of stations across south Asia, which has not been carried out thus far. We focus on the pre-monsoon season (March-May) for the study, as O 3 mixing ratios at the surface are generally the highest over most of south Asia during this period (Jain et al, 2005;Debaje et al, 2006;Reddy et al, 2010;Ojha et al, 2012;Gaur et al, 2014;Renuka et al, 2014;Bhuyan et al, 2014;Sarangi et al, 2014;Yadav et al, 2014;Sarkar et al, 2015). This is because photochemistry over south Asia is most intense during this season due to the combined effects of high pollution loading, biomass-burning emissions and a lack of precipitation.…”
mentioning
confidence: 99%
“…Set-up of all these instruments is shown in Fig. 8 while their detailed descriptions are given by Sarangi et al (2014).…”
Section: Instruments For Trace Gasesmentioning
confidence: 99%
“…These instruments are regularly subjected to zero and span tests using internal ozone generator and ozone observations from both the instruments are also inter-compared by running them side by side and using a common inlet. Further details of such inter-comparisons 20 are reported in Sarangi et al (2014). CO measurements are conducted using analyzers from two make viz., Horiba APMA-370 (at Bode and Pantnagar) and Thermo 48i (at Nainital).…”
mentioning
confidence: 99%
“…Regular zero check and span check for CO instruments are performed using a primary calibration mixture from Linde UK (1150 ppbv; Sarangi et al, 2016) and secondary gas from Chemtron Science Laboratories (1790 ppbv). Multipoint calibrations (ultra-pure gases) are also carried out in different observational ranges using a zero air generator 10 (Thermo model 1160) and a dynamic gas calibrator (Thermo model 146i) (Sarangi et al, 2014).…”
mentioning
confidence: 99%